Technology and wage share of older workers - Donghyun Park; Kwanho Shin (Asian Development Bank (ADB), 2023)
Technological progress may be less beneficial for older workers than younger workers. In this paper, we empirically examine the impact of technological change on the wage share of older workers. More specifically, we look at five different types of technological advancement using data from 30 European and Asian countries that are at the forefront of global population aging. Our findings indicate that recent technological developments centered on information and communication technology, software, and robots do not adversely affect older workers. One possible explanation is that older workers may be more open to learning and adopting new technologies than widely presumed.1
Keywords: E24; E25; J01; J11; O11; 330; aging; older workers; wage share; capital; information communication technologies; robots